DINAMIKA KOMUNIKASI SOSIAL JASA ANGKUTAN UMUM (On line dan Konvensional) - Prayoga, Boby Indra (Universitas Merdeka Malang, 2017)
Abstract Social Reality related to the business of this online system can also have an impact on the social life of the community, where the community is more facilitated in terms of service at a cheaper cost. So that most people who understand the technology will prefer to conduct business transactions through the online system. Included in the business of public transport services, whether it is two-wheel or four-wheel or more, such as Gojek, Uber, Grab and others. All depend on technology to meet the needs through online systems. But the impact on society that provides public transportation services with conventional system, thus causing conflict horizontally in the level of the community. This research method uses literature study on the phenomenon of social dynamics of public transport services both conventional and on line.Untuk author tries to conduct studies which is a phenomenon of the impact of technological development on the gap in the community at the same level, so the conflict among the business actors of public transport services. Conflicts arising in the form of contradictory opposition to; or at loggerheads. The dynamics of social communication generated from the policies that are not pro-society. Keywords: Social Dynamics, Social Communication and Public Transportation ServicesDOI : https://doi.org/10.26905/nomosleca.v3i2.2038